On energetic and dissipative gradient effects within higher-order strain gradient plasticity: Size effect, passivation effect, and Bauschinger effect. (June 2021) - Hua, Fenfei; Liu, Dabiao; Li, Yuan; He, Yuming; Dunstan, D.J.
Abstract: The size effect, the passivation effect, and the plastic behavior under non-proportional loading in the context of bending and tension of thin foils, and a combination of compression and shear of constrained layers, are studied using Gudmundson's higher-order strain gradient visco-plasticity theory. Bending experiments on thin nickel foils with and without passivation are performed with a load-unload technique. The passivated layer increases the flow stress significantly. Finite element simulations are carried out on elasto-viscoplastic foils under bending and tension, and on constrained layers under combined compression and shear. The simulation results are generally in agreement with the experimental observations. Implications for higher-order boundary conditions and the roles of energetic and dissipative gradient terms are highlighted. The dissipative gradient terms contribute to the increased yield strength, whereas the energetic gradient terms lead to increased strain hardening and an anomalous Bauschinger effect. The modeling of the deformation of constrained layers suggests that compressive stress has a significant influence on the shear flow stress, reducing it compared with the shear flow stress under pure shear. Highlights: Bending tests on thin nickel foils show that the passivated layer increases the yield strength and the flow stress. Size effect, passivation effect, and Bauschinger effect are studied using Gudmundson's SGP theory. Implications for the higher-order boundary conditions, and the roles of energetic and dissipative gradients are highlighted.